Robust estimation of 1D shear-wave quality factor profiles for site response analysis using seismic noise. Issue 161 (October 2022) - Dreossi, Ilaria; Parolai, Stefano
Abstract: Ambient seismic noise, particularly useful in urban areas, contains valuable information on seismic wave attenuation and the related shear-wave quality factor ( Q S ) in the near-surface layers. Although the application of ambient seismic noise for attenuation studies is promising, more development and testing are necessary before it can be adopted for standard in situ analysis. In this paper, a development of the approach suggested in Parolai (2014) [58] is proposed and tested to improve the robustness of the results. In particular, the Simultaneous Algebraic Reconstruction Technique (SART) (Andersen and Kak, 1984) [5] is used for implementing an attenuation positivity constraint to the solutions ― to non-get negative Q S values ― avoiding the preliminary testing of parameters required in the original procedure. Tests carried out at sites, where previous Q S values estimated with the approach proposed by Parolai (2014) [58] were available, show similar results to the former algorithm. Furthermore, for the used data sets, the attenuation positivity constraint was shown not to be mandatory for gaining solutions with a physical meaning. Highlights: S-wave quality factor can be estimated by seismic noise for site response analysis. S-wave quality factor can be obtained without positivity constraint using SART. Site characterization can be improved by seismic noise measurements in urban areas.